HUBUNGAN SIKAP IBU DENGAN KESIAPAN TOILET TRAINING DI PAUD AVICENA YOGYAKARTA - Suryati; Nita Ana Pratiwi (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Toddler age children are in important concept in the growth process. That age is the right time for children to learn various skills, such as learning to defecate and urinate. In do defecate and urinate in toddler need preparation by physical, psychological, and intellectual. The attitude of mother determines the children to use toilet training. Objective:This research is aim to determine the relationship of mother’s attitude with the readiness of toilet training in PAUD Avicena Yogyakarta Methods: This research design is descriptive correlational with cross-sectional approach. The sample of this research was 32 respondents taken with total sampling technique. The data collection is use questionnares with hypothesis testing technique using Chi Square test Results:This research shows that the majority of mother’s attitude in use of diapers in the postive category (84,4%), the readiness of toilet training majority are in category less ( 53,1%) Chi Square correlation value between mother’s attitude in use of diapers to the toilet training readiness is p value 0,000 < 0,05 Conclusion:The more attitude of the mother in supports of using diapers, it will be influential in less toilet training readiness in toddler children Keywords: Attitude, Toilet Training Readiness